MANAJEMEN HUMAS DALAM MENINGKATKAN SOSIALISASI VISI DAN MISI INSTITUT AGAMA ISLAM SUNAN KALIJOGO JABUNG MALANG - Endang Tyasmaning (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Public Relations Management can be described as a form of process of directing and giving an influence to the activities contained in a group of members and whose duties and functions are interrelated. In this study, researchers used qualitative case study research to collect research data using interviews and literacy studies according to the research title, and in data analysis using descriptive techniques As a leader, you can not only order your co-workers what to do, but also influence your subordinates and carry out some of their orders. As for supervision in public relations management, namely the socialization of the vision and mission at the Islamic Institute of Sunan Kalijogo Jabung Malang, then carrying out optimal monitoring activities and requiring data or information related to public relations management. Supervision that has been implemented by the Chancellor of the Islamic Institute of Sunan Kalijogo Malang, namely the realization of a public relations management work program. And for the organization of public relations, namely how the work is allocated among academicians. From the above description is the essence of organizing public relations management, which includes several things including; First, detailing the work in planning public relations management, second, organizing public relations management, third, actualizing public relations management, fourth, supervising public relations management.